The Needs Analysis of Maritime English teaching Materials Development for D4 Nautical Study Program of the Indonesian State Maritime Polytechnic (Polimarin): - Marselia Marselia; Mahsunah etik Rahayuningsih (PPPM Polimarin, 2021)
It is a Research and Development study. This study aims to present the results of the needs analysis of Maritime English teaching materials in the D4 Nautical Study Program of the Indonesian State Maritime Polytechnic (Polimarin). The data in this study were obtained through a questionnaire was distributed and filled in by 60 respondents, namely active students of the D4 Polimarin Nautical Study Program. In addition, interviews were also conducted with lecturers who teach Maritime English and the Head of the D4 Nautical Study Program. The obtained data were analyzed qualitatively using needs analysis. The results of the analysis of the teaching material needs obtained show that basically the teaching materials have been provided by the lecturers, but have not been provided systematically in form of module or book. Students do not have teaching materials to handle and study them at home. The findings of this study will be used to develop and improve Maritime English teaching materials in the D4 Nautical study program. In the future, teaching materials will be developed in the form of module according to student needs in line with the applicable curriculum.